The Effectiveness of the Contextual Teaching and Learning (CTL) Model in Improving Elementary School Students' Fraction Problem-Solving Ability - Dina Rahma Wardana; Desty Arfiyani; Febriana Nur Cahyaningrum; Ayu Made Juniwati Wiratha; Kurniatun Nisak; Jauharul Ifadhi; Cholifah Tur Rosidah; Rosmiati Rosmiati (Assyfa Journal of Islamic Studies, 2026)
This study aims to determine the effectiveness of the Contextual Teaching and Learning (CTL) model in improving the mathematical problem-solving skills of fourth-grade students at SDN Mekar Jaya 31 in Depok regarding fractions. The study employed a quantitative approach with a one-group pretest-posttest design. The study sample consisted of 32 fourth-grade students. Data collection techniques included tests, observations, and documentation. Tests were used to measure students' mathematical problem-solving skills before and after the implementation of the CTL model, while observations and documentation were used to support data on the implementation of the learning process. The results of the study indicate that the implementation of the CTL model was able to improve students' mathematical problem-solving skills in the topic of fractions. This was demonstrated by an increase in students' learning outcomes from the pretest to the posttest scores. The results of the paired-sample t-test also showed a significant difference between the scores before and after the intervention. These findings indicate that instruction using the CTL model is effective because it helps students understand the concept of fractions through real-life contexts, encourages active student engagement, and facilitates students' ability to develop problem-solving strategies. Thus, the CTL model can serve as an effective instructional alternative for improving elementary school students' mathematical problem-solving skills, particularly in the topic of fractions.